2017
DOI: 10.1111/cpr.12329
|View full text |Cite
|
Sign up to set email alerts
|

NEAT1: A novel cancer‐related long non‐coding RNA

Abstract: Aberrant overexpression of the long non-coding RNA NEAT1 (nuclear paraspeckle assembly transcript 1) has been documented in different types of solid tumours, such as lung cancer, oesophageal cancer, colorectal cancer and hepatocellular carcinoma, in which its high levels are associated with poor prognosis. In contrast, NEAT1 is downregulated in acute promyelocytic leukaemia where it promotes leucocyte differentiation. In this review, we provide an overview of current evidence concerning the oncogenic role and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
205
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 249 publications
(215 citation statements)
references
References 54 publications
(51 reference statements)
10
205
0
Order By: Relevance
“…Currently, there are no ideal biomarkers, which can be used in screening oesophageal cancer strategies . LncRNA nuclear paraspeckle assembly transcript 1 (NEAT1), LncRNA ANRIL, HOX transcript anti‐sense intergenic RNA (HOTAIR) and SOX2 overlapping transcript (SOX2OT) were found to be associated with oesophageal cancer …”
Section: Oesophageal Cancermentioning
confidence: 99%
“…Currently, there are no ideal biomarkers, which can be used in screening oesophageal cancer strategies . LncRNA nuclear paraspeckle assembly transcript 1 (NEAT1), LncRNA ANRIL, HOX transcript anti‐sense intergenic RNA (HOTAIR) and SOX2 overlapping transcript (SOX2OT) were found to be associated with oesophageal cancer …”
Section: Oesophageal Cancermentioning
confidence: 99%
“…The nuclear paraspeckle assembly transcript 1 (NEAT1) was a newly identified lncRNA that regulated gene expression by retaining mRNAs for editing in the nucleus (Clemson et al, ). It was reported as an oncogene in several types of human cancers, including hepatocellular carcinoma, lung cancer, oesophageal cancer, colorectal cancer, renal cell carcinoma, ovarian cancer, breast cancer, and glioma (F. Liu et al, ; Y. Liu, Wang, Fu, & Lu, ; Yu, Li, Zheng, Chan, & Wu, ; Zhou et al, ). However, the role of NEAT1 in RB remains unknown.…”
Section: Introductionmentioning
confidence: 99%
“…[7][8][9][10][11][12] However, mutation of lncRNAs will cause cancer initiation and promote the metastasis of malignancy. [13][14][15] For instance, lncRNA metastasis-associated lung adenocarcinoma transcript 1 (MALAT1) was first found in lung cancer metastasis. Many studies had demonstrated that lncRNA MALAT1 was overexpressed in various cancer, and it might act as a potential biomarker and therapeutic target in cancer treatment.…”
Section: Introductionmentioning
confidence: 99%